2022
DOI: 10.1021/acssuschemeng.2c04284
|View full text |Cite
|
Sign up to set email alerts
|

Lignin: A Sustainable Antiviral Coating Material

Abstract: Transmission of viruses through contact with contaminated surfaces is an important pathway for the spread of infections. Antiviral surface coatings are useful to minimize such risks. Current state-of-the-art approaches toward antiviral surface coatings either involve metal-based materials or complex synthetic polymers. These approaches, however, even if successful, will have to face great challenges when it comes to large-scale applications and their environmental sustainability. Here, an antiviral surface coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…In a recent study, antiviral lignin surface coatings made of water insoluble lignins were prepared, which showed very efficient inactivation of HSV-2 (>99% after 30 min). Particular attention has been focused on the mechanism behind the antiviral activity of these coatings, which turned out to be strongly related to the lignin phenol content . The COVID-19 outbreak has highlighted the importance of antiviral surfaces.…”
Section: Lignin As Antimicrobial Agentmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, antiviral lignin surface coatings made of water insoluble lignins were prepared, which showed very efficient inactivation of HSV-2 (>99% after 30 min). Particular attention has been focused on the mechanism behind the antiviral activity of these coatings, which turned out to be strongly related to the lignin phenol content . The COVID-19 outbreak has highlighted the importance of antiviral surfaces.…”
Section: Lignin As Antimicrobial Agentmentioning
confidence: 99%
“…Particular attention has been focused on the mechanism behind the antiviral activity of these coatings, which turned out to be strongly related to the lignin phenol content. 105 The COVID-19 outbreak has highlighted the importance of antiviral surfaces. Lignin is a promising material to develop affordable and sustainable antiviral coatings on a large scale, which deserves additional investigation.…”
Section: Lignin As Antimicrobial Agentmentioning
confidence: 99%
“…Boarino et al showed that lignin is effective against Herpes Simplex Virus type 2 (HSV-2). Lignin can be used as a cost-effective and environmentally sustainable polymer-based antiviral and antimicrobial coating [ 68 ].…”
Section: Current Antiviral Surface Coating Techniquesmentioning
confidence: 99%
“…Moreover, the coatings of such particles applied through other water-based methods typically show poor adhesion to the substrate and low cohesion, arising from the insufficient contact of the particles with the substrate and with each other. Moreover, the use of toxic organic solvents such as dioxane to facilitate the application of lignin coatings [ 13 , 23 ] is inconsistent with the current emphasis on green and safe industrial practices and products. By contrast, commercial tannins are water-soluble at room temperature, making them suitable only for coatings for which water resistance is not required, such as single-use hygienic garments or curtains.…”
Section: Introductionmentioning
confidence: 99%